Судьба авторитета в современном мире - Бурлачук, В. (Социология: теория, методы, маркетинг, 2000)
The establishment of democratic power institutions has caused the substitution of
anonymous kind of power for that of totalitarianism. Studying crisis as a process of the
established world order disintegration sets the task of elucidating the effect of the
social mechanisms which participate in preserving the social reality and prevents its
complete disorientation. Authority, as well as tradition, should be used to curb the
elemental forces which have gone out of the social control, and offer an individual a set
of values, emotional orientations, rules and standards of behavior which can become
the means of achieving social peace.